Genome-wide scan identifies candidate loci related to remifentanil requirements during laparoscopic-assisted colectomy. (January 2018) - Nishizawa, Daisuke; Mieda, Tsutomu; Tsujita, Miki; Nakagawa, Hideyuki; Yamaguchi, Shigeki; Kasai, Shinya; Hasegawa, Junko; Fukuda, Ken-ichi; Kitamura, Akira; Hayashida, Masakazu; Ikeda, Kazutaka
Aim:  Opioids are widely used as effective analgesics, but opioid sensitivity is well known to vary widely among individuals. We explored the genetic factors that contribute to individual differences in intraoperative opioid sensitivity by performing a genome-wide association study.Patients & methods: We conducted a multistage genome-wide association study in subjects who underwent laparoscopic-assisted colectomy.Results: A nonsynonymous SNP, rs199670311, within the TMEM8A gene region and intronic SNPs, including rs4839603, within the SLC9A9 gene region were significantly associated with intraoperative opioid requirements (p = 3.409 × 10 -8 in the dominant model for rs199670311; p = 4.162 × 10 -6 and p = 4.229 × 10 -6 in the additive and recessive models, respectively, for rs4839603). The A and T alleles of the rs199670311 and rs4839603 SNPs, respectively, were associated with lower opioid sensitivity in patients.Conclusion: Our findings provide valuable information for personalized pain treatment during laparoscopic-assisted colectomy.